Rapid and Visual Differentiation of Mycobacterium tuberculosis From the Mycobacterium tuberculosis Complex Using Multiplex Loop-Mediated Isothermal Amplification Coupled With a Nanoparticle-Based Lateral Flow Biosensor - Yang, Xinggui; Huang, Junfei; Chen, Xu; Xiao, Ziyu; Wang, Xiaojuan; Chen, Yijiang; Zheng, Wenlin; Chen, Wei; Chen, Huijuan; Lei, Shiguang; Hu, Yong; Li, Shijun (Frontiers in Microbiology, 2021)
Tuberculosis (TB) is a chronic infectious disease mainly caused by Mycobacterium tuberculosis (MTB), but other members of the Mycobacterium tuberculosis complex (MTBC), especially M. bovis (pyrazinamide-resistant organisms), may also be involved. Thus, the ability to rapidly detect and identify MTB from other MTBC members (e.g., M. bovis, M. microti, M. africanum) is essential for the prevention and treatment of TB. A novel diagnostic method for the rapid detection and differentiation of MTB, which employs multiplex loop-mediated isothermal amplification (mLAMP) combined with a nanoparticle-based lateral flow biosensor (LFB), was established (mLAMP-LFB). Two sets of specific primers that target the IS6110 and mtp40 genes were designed according to the principle of LAMP. Various pathogens were used to optimize and evaluate the mLAMP-LFB assay. The optimal conditions for mLAMP-LFB were determined to be 66°C and 40 min, and the amplicons were directly verified by observing the test lines on the biosensor. The LAMP assay limit of detection (LoD) was 125 fg per vessel for the pure genomic DNA of MTB and 4.8 × 103 CFU/ml for the sputum samples, and the analytical specificity was 100%. In addition, the whole process, including the clinical specimen processing (35 minutes), isothermal amplification (40 minutes) and result confirmation (1-2 minutes), could be completed in approximately 80 minutes. Thus, mLAMP-LFB is a rapid, reliable and sensitive method that is able to detect representative members of MTBC and simultaneously differentiate MTB from other MTBC members, and it can be used as a potential screening tool for TB in clinical, field and basic laboratory settings.